Legal Policy in the Implementation of Rehabilitation for Drug Addicts in Lampung Province - Zainab Ompu Jainah (IHSA Institute, 2022)
The purpose of this study was to find out and analyze how big a pregnant woman's marriage and the status of The problem of narcotics circulation becomes so important given that narcotic drugs are drugs that have an influence on the physical and mental, Narcotics addicts and drug abusers are obliged to undergo medical rehabilitation and social rehabilitation in the center of narcotic dependence rehabilitation. With medical rehabilitation and social rehabilitation is intended to restore and develop the physical, mental and social abilities of the addict. The approach method used in this study is normative legal research including research on legal principles. Rehabilitation efforts for addicts and victims of narcotics abuse carried out currently the drug rehabilitation program at BNNP Lampung are carried out in three forms First, outpatient rehabilitation, Outpatient rehabilitation is a periodic counseling examination in approximately three months. obstacles in cases of narcotics abuse are differences in perceptions between law enforcement officers, Lack of understanding of the community, Apathy of the community Limitations of human resources Skilled and trained officers (counselors and assessors), infrastructure that is not optimally available, There is a need for mapping, socialization and education for all stakeholders